Congenital myasthenic syndrome due to a TOR1AIP1 mutation: a new disease pathway for impaired synaptic transmission. Issue 2 (18th October 2020) - Cossins, Judith; Webster, Richard; Maxwell, Susan; Rodríguez Cruz, Pedro M; Knight, Ravi; Llewelyn, John Gareth; Shin, Ji-Yeon; Palace, Jacqueline; Beeson, David
Abstract: Congenital myasthenic syndromes are inherited disorders characterized by fatiguable muscle weakness resulting from impaired signal transmission at the neuromuscular junction. Causative mutations have been identified in genes that can affect the synaptic function or structure. We identified a homozygous frameshift deletion c.127delC, p. Pro43fs in TOR1AIP1 in two siblings with limb-girdle weakness and impaired transmission at the neuromuscular synapse. TOR1AIP1 encodes the inner nuclear membrane protein lamin-associated protein 1. On muscle biopsy from the index case, lamin-associated protein 1 was absent from myonuclei. A mouse model with lamin-associated protein 1 conditionally knocked out in striated muscle was used to analyse the role of lamin-associated protein 1 in synaptic dysfunction. Model mice develop fatiguable muscle weakness as demonstrated by using an inverted screen hang test. Electromyography on the mice revealed a decrement on repetitive nerve stimulation. Ex vivo analysis of hemi- diaphragm preparations showed both miniature and evoked end-plate potential half-widths were prolonged which was associated with upregulation of the foetal acetylcholine receptor γ subunit. Neuromuscular junctions on extensor digitorum longus muscles were enlarged and fragmented, and the number of subsynaptic nuclei was significantly increased. Following these findings, electromyography was performed on cases of other nuclear envelopathies caused by mutations in LaminA/C or emerin, but decrement on repetitive nerve stimulation or other indications of defective neuromuscular transmission were not seen. Thus, this report highlights the first nuclear membrane protein in which defective function can lead to impaired synaptic transmission. Abstract : A mutation in TOR1AIP1 causes a new type of congenital myasthenic syndrome, characterized by limb girdle fatiguable muscle weakness and compound muscle action potential decrement on repetitive nerve stimulation. A mouse knockout model shows impaired neurotransmission, fragmented neuromuscular junctions, increased synaptic nuclei and up-regulation of foetal acetylcholine receptors. Graphical Abstract: